(untitled) (Research, Society and Development, 2023)
Neurodegenerative diseases and/or disorders, as well as pediatric neuropathies and neuropsychiatric disorders are multicausal and have in common the direct or indirect impact on the performance of activities of daily living, whether for psychological, social or economic reasons for the individual and family. The current treatments available are generally pharmacological for symptom control and progression delay, not encompassing disease regression or prevention. Due to the need for new therapeutic approaches in recent years, there has been an increase in the number of studies involving herbal medicines derived from plants with anti-inflammatory and antioxidant bioactive potential, which provides alternative and economic methods for the population. Among plants with therapeutic potential, Cannabis sativa has become the focus of research because it has more than 560 constituents with therapeutic potential for the treatment and relief of symptoms in serious diseases, such as CBD and THC cannabinoids. This potential can be explained by its ability to interact with the cannabinoid system, an important regulator of physiological processes in the human body, composed of eCBs, AEA and 2-AG that couple to CB1 and CB2 receptors present in the CNS and PNS. These receptors are G protein-coupled, therefore C. sativa cannabinoids have the potential to interact with G protein receptors, being able to interact with neurotransmitters and neuromodulators involved in psychomotor coordination, memory, mood and pain. In view of the above, the present study aimed to collect and analyze qualitative and quantitative data for the analysis of Cannabis sativa in therapeutics against neuropathologies, neuropsychiatric disorders and neurodegenerative diseases. The present study is an exploratory and qualitative-quantitative research carried out through a survey of data for scientific and technological prospection during the period from October 20, 2021 to July 20, 2022. To search for articles PubMed and ScienceDirect databases were used. Meanwhile, the EPO, WIPO and INPI databases were used for patent searches. The analysis continued with the identification of relevant publications based on the presence of keywords in the title or abstract. As a result, the qualitative-quantitative study exposed a low number of patents and articles related to the subject, which may be justified due to the use of opioids as a mechanism of medicinal treatment still being a target of studies, despite having millenary records of the use of this plant in specific for medicinal purposes in Asia, which highlights the importance of developing new studies to evaluate in vitro and in vivo the agonist activity of the compounds exposed above. Therefore, it is possible to conclude, given the above, that phytocannabinoids have potential for the treatment of neuropathies, neuropsychiatric disorders and neurodegenerative diseases.